Structural and physicochemical aspects of drug release from layered double hydroxides and layered hydroxide salts - Rojas Delgado, Ricardo (2015)
Layered double hydroxides (LDHs) and Zn layered hydroxide salts (LHSs) present different physicochemical and interfacial properties derived from their dissimilar structure and composition, which affect the release behavior of the intercalated drug. In this work, these aspects are studied using LDHs and LHSs intercalated with ibuprofen (Ibu), naproxen (Nap) or ketoprofen (Ket) to understand the behavior of intercalation compounds as drug carriers. The structure of the solids and the interaction mode between the drugs and the layers were determined by chemical analysis, PXRD, FTIR and NMR. Further, the interfacial properties (potential zeta and hydrophilic/hydrophobic character) of the solids, as well as their drug release profiles were also comparatively studied. The drugs were attached by electrostatic interactions to LDH layers while coordinate bond was produced in the case of LHSs. The different interaction modes, together with the higher drug density between LHS layers produced more crystalline solids with larger basal spacing values than the corresponding LDH. This detailed structural study allowed for establishing the correlations between structure, interactions, morphology, interfacial properties and drug release behavior. Thus, the different interaction modes determined the surface charging behavior, while the solubility of LHS layers led to a fast drug release in neutral media. Finally, the loose drug arrangement in the hybrids caused a solubility increase in acid media. These correlations are helpful to predict and optimize the behavior of drug delivery systems based on both LDHs and Zn–LHSs.